NETWORKING AS A TOOL OF CAREER SELF-DETERMINATION OF FU-TURE TEACHERS IN THE SPHERE OF PHYSICAL CULTURE AND SPORT - Rezanovich, I.V.; Cherepov, E.A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a theoretical analysis and test the effectiveness of networking for career self-determination of future teachers in the field of physical culture and sports. Methods and structure of the study. The experiment took place on the basis of two universities in Voronezh and Chelyabinsk, 194 students of 3-4 courses took part in it. For two years, networking of various modifications was included in each event. The following diagnostic tools were chosen: “Methodology for measuring career self-determination” (A.N. Demin, A.B. Sedykh, B.R. Sedykh); author's development "Strategic career map" and student surveys. Results and conclusions. The use of networking made it possible to significantly reduce the students' need for information about potential jobs, increase their professional motivation, confidence in their chosen profession and their abilities. A significant decrease in job changes in the first year after graduation was recorded. According to the modern “social-cognitive theory of career” (R. Lent, S. Brown and G. Hackett), the results obtained are largely due to the expansion of individual professional contacts of each student, which allowed students to better know the intricacies of the profession, get an external assessment of their abilities, claims and plans, and often support from more experienced professionals.